The Third Rail of Pediatric Communication: Discussing Firearm Risk and Safety in Well-Child Exams. Issue 4 (21st March 2021) - Hinnant, Amanda; Boman, Courtney D.; Hu, Sisi; Ashley, Rokeshia Renné; Lee, Sungkyoung; Dodd, Sherry; Garbutt, Jane M.; Cameron, Glen T.
ABSTRACT: This research endeavors to understand how pediatricians and parents discuss – or do not discuss – firearm risks for children during well-child visits. Through individual semi-structured interviews with 16 pediatric providers and 20 parents, the research explores discursive barriers to open conversation, perspectives on anticipatory guidance, and new ideas for culturally competent messaging. The research focuses particularly on how parents' and providers' perspectives on firearm risk communication are tied to cultural norms and expectations. One salient theme that emerged is that the American Academy of Pediatrics recommendation that pediatricians ask parents about ownership status is deemed undesirable by pediatricians and parents because of the delicate intercultural setting. Born out of pediatric and parent experiences, and mindful of culturally salient barriers, this study offers alternative strategies for discussing firearm risk in well-child exams.